Hydrochemical zoning of valley peatlands as a result of water supply conditions: examples from Poland - Ziułkiewicz, Maciej; Fortuniak, Anna (Geology, Geophysics and Environment, 2016)
The chemical composition of water from two peatlands was investigated. Both peatlands, which are nature reserves, are located in central Poland in the Widawka and Rawka River valleys. The study concerned groundwaters, peat waters from different depths, and waters from draining ditches. The research permitted determination of the hydrochemical zoning of the peatlands resulting from the complex character of the water supply. The hydrochemical interpretation of surface waters outflowing alongside the ditches, in terms of their similarity to particular zones, provides an insight into the water-feeding structure of the peatlands. In the evaluation, hydrochemical indicators were applied, which have been used in hydrogeological studies. They are based on equivalent concentrations of the major ions: sodium, calcium, chlorides, and sulphates, selected from other hydrochemical elements by means of principal component analysis (PCA), conducted individually for each peatland. The analyses showed a high contribution of unconfined and confined groundwaters to the water supply, with clearly distinguishable zones, in terms of their transit through the structures of the peatlands.